IMPROVING THE QUALITY AND EFFICIENCY OF TEACHING EFL IN ENGLISH - Bozorova Zarina; Teshaboyeva Ziyoda (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
It is stated generally in the given article some problematic situations in education system that schools are facing nowadays, together with the ways to tackle issues. Moreover, innovative methods and styles are suggested in order to increase the quality of education.